2016
DOI: 10.1007/s00335-016-9644-9
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing reveals a nebulin nonsense mutation in a dog model of nemaline myopathy

Abstract: Nemaline myopathy (NM) is a congenital muscle disorder associated with muscle weakness, hypotonia, and rod bodies in the skeletal muscle fibers. Mutations in 10 genes have been implicated in human NM, but spontaneous cases in dogs have not been genetically characterized. We identified a novel recessive myopathy in a family of line-bred American bulldogs (ABDs); rod bodies in muscle biopsies established this as NM. Using SNP profiles from the nuclear family, we evaluated inheritance patterns at candidate loci a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…This is not unlike the hypothesis put forward for tremor generation in Charcot-Marie-Tooth (CMT) disease, where weight-invariant postural tremors may be present. A search of the literature for mutations in additional sarcomeric proteins associated with myopathy and tremor revealed further cases of patients with mutations in genes encoding thick (MYH2 and MYL2) and thin (TNNT1, TPM3, and NEB) filament proteins (Supplementary Table 2), [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] suggesting that crossbridge dysregulation may emerge as a myogenic tremor generator beyond the MYBPC1 mutations reported here. Given that our patients do not have a neuropathy and MYBPC1 is expressed purely in skeletal muscle, we hypothesize instead that the tremor is sarcomeric and hence myogenic in origin, but, similar to the denervation tremor, is then picked up by stretch receptors, where it undergoes centrally looped propagation and enhancement, thereby rendering it clinically visible.…”
Section: Discussionmentioning
confidence: 99%
“…This is not unlike the hypothesis put forward for tremor generation in Charcot-Marie-Tooth (CMT) disease, where weight-invariant postural tremors may be present. A search of the literature for mutations in additional sarcomeric proteins associated with myopathy and tremor revealed further cases of patients with mutations in genes encoding thick (MYH2 and MYL2) and thin (TNNT1, TPM3, and NEB) filament proteins (Supplementary Table 2), [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] suggesting that crossbridge dysregulation may emerge as a myogenic tremor generator beyond the MYBPC1 mutations reported here. Given that our patients do not have a neuropathy and MYBPC1 is expressed purely in skeletal muscle, we hypothesize instead that the tremor is sarcomeric and hence myogenic in origin, but, similar to the denervation tremor, is then picked up by stretch receptors, where it undergoes centrally looped propagation and enhancement, thereby rendering it clinically visible.…”
Section: Discussionmentioning
confidence: 99%
“…It was an advantageous choice over transcriptome sequencing in this study because SGCD transcripts would have been absent in case 3 and possibly case 1 as well, necessitating additional sequencing of SGCD to identify the causative mutations. In dogs, WES has led to the identification of alleles underlying progressive retinal atrophy, primary angle closure glaucoma, and nemaline rod myopathy using small numbers of related cases [34][35][36][37][38] but is not ideal for detecting intergenic deletions or genomic rearrangements [39]. The development of improved WES enrichment kits for dogs [39,40] will facilitate future detection of disease variants in canine models.…”
Section: Discussionmentioning
confidence: 99%
“…Whole exome sequencing (WES) has been extensively applied in human medicine for several diseases and recent studies have identified potential therapeutic targetable mutations in MM . In dogs, investigations to identify global somatic mutations by next generation sequencing (NGS) were previously conducted in lymphoma and in rare congenital, retinal and neurodegenerative disorders. Recently, two extensive NGS studies have been conducted in canine MM to map the genomic landscape of this tumour but progression after therapy were not described …”
Section: Introductionmentioning
confidence: 99%